Internet Health Report 2019 - Mozilla Foundation (Einzelveröffentlichungen Sozialwissenschaften, 2019)
This annual report is a call to action to recognize the things that are having an impact on the internet today, and to embrace the notion that we as humans can change how we make money, govern societies, and interact with one another online. We invite you to participate in setting an agenda for how we can work together to create an internet that truly puts people first. This book is neither a country-level index nor a doomsday clock. Our intention is to show that while the worldwide consequences of getting things wrong with the internet could be huge - for peace and security, for political and individual freedoms, for human equality - the problems are never so great that nothing can be done. More people than you imagine are working to make the internet healthier by applying their skills, creativity, and personal bravery to business, technology, activism, policy and regulation, education, and community development. This annual report is a call to action to recognize the things that are having an impact on the internet today, and to embrace the notion that we as humans can change how we make money, govern societies, and interact with one another online. We invite you to participate in setting an agenda for how we can work together to create an internet that truly puts people first. This book is neither a country-level index nor a doomsday clock. Our intention is to show that while the worldwide consequences of getting things wrong with the internet could be huge - for peace and security, for political and individual freedoms, for human equality - the problems are never so great that nothing can be done. More people than you imagine are working to make the internet healthier by applying their skills, creativity, and personal bravery to business, technology, activism, policy and regulation, education, and community development.